Effects of construction waste clay bricks on growth of pepper and improvement of clay properties (Bangladesh Journal of Botany, 2023)
Pot experiment, indoor detection and triaxial experiment were carried out to study the effects of construction waste clay bricks on the growth of pepper and improvement of clay nutrient and strength properties. The clay from southern Shaanxi was rolled and screened by 2mm, and the construction waste clay bricks were ground to 0-2, 2-5 and 5-7 mm. Construction waste with different particle sizes was mixed with clay in a mass ratio of 0:1 (CK), 1:1, 1:2, and 1:3. Construction waste accounted for 0, 50, 33 and 25% in the four mixed matrices, respectively. About 33~50% construction waste clay bricks with particle size of 5~7mm mixed with pure clay showed higher nutrient levels than that of pure clay. The plant height and yield of cultured pepper were the highest in construction waste clay bricks of 33~50%, with particle size of 5~7mm mixed with pure clay and the soil strength 33.2% higher than that of pure clay.  This treatment provides sufficient nutrient conditions for plant growth. This not only provides sufficient nutrient conditions for pepper growth, but also meets the corresponding shear strength and suitability for clay area soil improvement, especially for clay slope stability improvement. The application value and prospect of using construction waste in land engineering construction and soil organic reconstruction and identified a new way of utilizing construction waste as a resource were explored.Bangladesh J. Bot. 52(2): 503-514, 2023 (June) Special